Determining the Impact of Socioeconomic Status and Distance to a Rural Tertiary-Care Center on Preterm Delivery [A219]. (May 2022) - Darivemula, Shilpa M.; Kouassi-Brou, Marilyn; Pollack, Catherine C.; Goodman, Daisy J.; Fisher, Timothy
Abstract : INTRODUCTION: Hospital-based labor and delivery units are closing at increasing rates in the rural U.S., with significant implications for maternal and newborn health. The goal of this analysis was to examine clinical, sociodemographic, and geographic risk factors for preterm delivery (PTD) at a single, rural, level III maternal obstetric care center. METHODS: This study was a retrospective electronic medical record review of singleton pregnancies delivering at Dartmouth-Hitchcock Medical Center in Lebanon, New Hampshire, U.S. between 2016 and 2018. The primary outcome was PTD (at less than 37 weeks of gestation), with secondary outcomes of low birth weight (LBW) and intensive care nursery (ICN) admission. The primary exposures included travel time and insurance carrier. Demographic and clinical covariates and ZIP code level socioeconomic data were incorporated into the multivariate models. RESULTS: Compared to patients traveling less than 30 minutes, patients traveling 1–1.5 hours had approximately twice the odds of PTD (odds ratio [OR, ], 2.08; 95% CI, 1.32–3.29; P =.002), birth of a LBW neonate (OR, 2.15; 95% CI, 1.29–3.58; P =.005), and infant admission to the ICN (OR, 1.83; 95% CI, 1.22–2.76; P =.004). Marital status, prenatal visit count, history of PTD, primiparity, and tobacco exposure also increased risks for PTD, LBW, and ICN admission. Insurance carrier status was not associated with increased odds of PTD, LBW, or ICN admission. CONCLUSION: This study suggests that rurality and its impact on maternal health is not just about distance from hospitals or degree of socioeconomic deprivation, but about local resource access as well.